(untitled) - Sutherland, Peter (London, 2006)
Lifelong learning has developed enormously as a distinct area of study within education in recent years not least because numerous governments and educational strategists have become very vocal supporters of new ways of learning throughout all stages of life. This up-to-the-minute guide to the topic brings together new writing from some of the leading thinkers in the field to offer a broad ranging and detailed snapshot of the position to date. The book provides a critical summary of current developments in understanding adult learning and the social context in which they are located. This provides a background for the framing of issues and the problems that emerge in institutional and non-formal contexts of lifelong learning. Students undertaking courses of study in this area as well as a wide range of undergraduate and postgraduate students in a variety of professional areas will find the material essential reading.
Keywords: Continuing education,Giáo dục cộng đồng